Price response, asymmetric information, and competition - Joshua Sherman; Avi Weiss (Bar-Ilan University, Department of Economics, 2012)
We compare predictions from a theoretical model based on the structure of the main outdoor retail market in Jerusalem with the results of an empirical analysis of price response to changes in cost. We find that firms without adjacent competition exhibit both upward and downward price rigidity, an outcome we ascribe to asymmetric information between the consumer and the firm. Given that previous studies have focused on downward price rigidities of firms with market power, our findings highlight the importance of accounting for transitory information asymmetries between the consumer and the firm when studying price rigidity.
Keywords: L11; L13; 330; price response; price rigidity; information asymmetry; market power; Einzelhandel; Preisrigidität; Asymmetrische Information; Marktmacht; Jerusalem